2016
DOI: 10.1155/2016/3089303
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Omega-3 Rich Diet on the Gut Microbiota

Abstract: Background. Recently, the importance of the gut microbiota in the pathogenesis of several disorders has gained clinical interests. Among exogenous factors affecting gut microbiome, diet appears to have the largest effect. Fatty acids, especially omega-3 polyunsaturated, ameliorate a range of several diseases, including cardiometabolic and inflammatory and cancer. Fatty acids associated beneficial effects may be mediated, to an important extent, through changes in gut microbiota composition. We sought to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 24 publications
5
102
0
2
Order By: Relevance
“…There has been only one case report of the effect of an omega-3 PUFA-rich diet on human intestinal microbiota 11. In this case, there was a notable increase in several SCFA (butyrate)-producing genera including Blautia , Bacterioides , Roseburia and Coprococcus 11…”
Section: Introductionmentioning
confidence: 91%
“…There has been only one case report of the effect of an omega-3 PUFA-rich diet on human intestinal microbiota 11. In this case, there was a notable increase in several SCFA (butyrate)-producing genera including Blautia , Bacterioides , Roseburia and Coprococcus 11…”
Section: Introductionmentioning
confidence: 91%
“…Last, using next-generation sequencing, the gut microbiome has been described and implicated in multiple disease processes, including GIB, 27 and its fingerprint can be modified by omega-3 administration. 28 Assessment of changes in the microbiome during omega-3 therapy may further elucidate the mechanism by which omega-3 suppresses GIB.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, on the fight against public health burden due to human's metabolic diseases around the world, the equilibrate n-6/n-3 ratio diet and/or seafood dietary ingestion is a healthy recommendation. It might be helpful and protect against the onset of metabolic syndrome in human population [39, 53, 54]. In the present study, beyond different possible mechanisms, it might also be a suggestive mechanism behind the metabolic amelioration observed in the MSG-obese mice.…”
Section: Discussionmentioning
confidence: 57%
“…These data indicate that PUFAs are able to induce programming in the offspring that provides a certain resistance against metabolic deterioration. A previous study using a similar ratio of n-6/n-3 fatty acids in pregnant rats has shown that the offspring exhibited an improvement in early brain development [6], and amelioration in metabolic impairment has been reported to be induced by PUFAs dietary consumption [39, 40]. The data presented herein suggest that n-6/n-3 fatty acids in a ratio of 1.2 : 1.0 exert by somehow a sort of protection attenuating the deleterious central effects of MSG treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation